2008
DOI: 10.1007/s11244-008-9089-9
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Reaction Enhancement: The Rapid Synthesis of SAPO-11 Molecular Sieves

Abstract: The effect of microwave and conventional heating methods on the nucleation and growth of SAPO-11 molecular sieve was investigated. Microwave synthesis enhances both the nucleation and growth of SAPO-11. The rate of heating primarily influences the nucleation time for both microwave and conventional heating. A more uniform morphology and narrower size distribution are formed using microwave heating compared to conventional. This suggests that rapid and even nucleation is the enhancement mechanism. Crystallizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 25 publications
0
35
0
1
Order By: Relevance
“…The higher activation energy calculated for microwave synthesized SAPO-11 (and AlPO-11) compared to conventional heating is due to the fact that microwave synthesis is activated by both thermal and non-thermal effects. [18] An increase in activation energy, for these reactions using microwave irradiation, is contrary to many reports that show a decrease in E a with microwave heating and hence accelerated rates due to a lower energy barrier. Furthermore, Gizdavic-Nikolaidis et al [42] reported an increase in the activation energy from conventional to microwave synthesis for NaA synthesis.…”
Section: Nucl Time a C H T U N G T R E N N U N G [Min]mentioning
confidence: 67%
See 4 more Smart Citations
“…The higher activation energy calculated for microwave synthesized SAPO-11 (and AlPO-11) compared to conventional heating is due to the fact that microwave synthesis is activated by both thermal and non-thermal effects. [18] An increase in activation energy, for these reactions using microwave irradiation, is contrary to many reports that show a decrease in E a with microwave heating and hence accelerated rates due to a lower energy barrier. Furthermore, Gizdavic-Nikolaidis et al [42] reported an increase in the activation energy from conventional to microwave synthesis for NaA synthesis.…”
Section: Nucl Time a C H T U N G T R E N N U N G [Min]mentioning
confidence: 67%
“…[18] A precursor solution was prepared by a mixture of two organic structure directing agents prepared by combining an aqueous solution consisting of 11.53 grams of 85 wt. % orthophosphoric acid and 22.0 grams of water with 6.9 grams of a hydrated aluminum oxide (a pseudo-boehmite, 74.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations